Green synthesis approach: extraction of chitosan from fungus mycelia. (December 2013) - Dhillon, Gurpreet Singh; Kaur, Surinder; Brar, Satinder Kaur; Verma, Mausam
Abstract : Chitosan, copolymer of glucosamine and N -acetyl glucosamine is mainly derived from chitin, which is present in cell walls of crustaceans and some other microorganisms, such as fungi. Chitosan is emerging as an important biopolymer having a broad range of applications in different fields. On a commercial scale, chitosan is mainly obtained from crustacean shells rather than from the fungal sources. The methods used for extraction of chitosan are laden with many disadvantages. Alternative options of producing chitosan from fungal biomass exist, in fact with superior physico-chemical properties. Researchers around the globe are attempting to commercialize chitosan production and extraction from fungal sources. Chitosan extracted from fungal sources has the potential to completely replace crustacean-derived chitosan. In this context, the present review discusses the potential of fungal biomass resulting from various biotechnological industries or grown on negative/low cost agricultural and industrial wastes and their by-products as an inexpensive source of chitosan. Biologically derived fungal chitosan offers promising advantages over the chitosan obtained from crustacean shells with respect to different physico-chemical attributes. The different aspects of fungal chitosan extraction methods and various parameters having an effect on the yield of chitosan are discussed in detail. This review also deals with essential attributes of chitosan for high value-added applications in different fields.